“Uso de herramientas digitales en la Cooperativa Ambato sede Latacunga, Provincia de Cotopaxi” - Chuquitarco Lagla, Lizeth Alexandra (2024)
The current research project deals about the digital tools use, which currently play a fundamental role in the work environment, since they help to make more effective work, at the moment ordering, managing and planning is for this, which the research project focuses on the activities planning carriyng out at the Ambato Cooperative, Latacunga headquarters, Cotopaxi province, with the aim by determining the digital tools use in said cooperative, thus starting at a quantitative analysis, which, it was applied a survey 23 closed questions to the workers, previously validated by academic professionals, this allowed them to know the digital tools used by the institution and how it intervenes in their work, what it was evinced, that the collaborators use tools, what provides the Cooperative and there is a need to use new digital tools, which contribute to the development its functions. At work, it could detect, what a workers considerable number, despite having other digital tools knowledge, do not use them to manage their work, for this, it was proposed three tools with distinct characteristics, but with the same aim, which is to help activities planning from Cooperative.